Reestructuración técnico administrativa de la empresa Europlast S.A.S. (2018)
The technical and administrative restructuring of the company Europlast, SAS, a diagnosis was made to recognize the current situation of the footwear subsector and the organization, for them tools such as PESTAL analysis and characterization of the sector were used to propose strategies through the matrix SWOT, where growth opportunities are evidenced for the organization. In the technical study, the five most significant references in sales and projection of the organization were studied, considerable reductions of standard times were obtained that allowed to take advantage of the installed capacity of the organization. In the administrative study, strategic planning was defined, its organizational structure and human talent activities were defined in turn. Finally, in the financial study, the impact of the restructuring was analyzed through a differential cash flow, obtaining a NPV of COP 31,749,664, therefore it is considered feasible and viable.